A First Study of the Virulence Potential of a Bacillus subtilis Isolate From Deep-Sea Hydrothermal Vent - Gu, Han-Jie; Sun, Qing-Lei; Luo, Jing-Chang; Zhang, Jian; Sun, Li (Frontiers in Cellular and Infection Microbiology, 2019)
Bacillus subtilis is the best studied Gram-positive bacterium, primarily as a model of cell differentiation and industrial exploitation. To date, little is known about the virulence of B. subtilis. In this study, we examined the virulence potential of a B. subtilis strain (G7) isolated from the Iheya North hydrothermal field of Okinawa Trough. G7 is aerobic, motile, endospore-forming, and requires NaCl for growth. The genome of G7 is composed of one circular chromosome of 4,216,133 base pairs with an average GC content of 43.72%. G7 contains 4,416 coding genes, 27.5% of which could not be annotated, and the remaining 72.5% were annotated with known or predicted functions in 25 different COG categories. Ten sets of 23S, 5S, and 16S ribosomal RNA operons, 86 tRNA and 14 sRNA genes, 50 tandem repeats, 41 mini-satellites, one microsatellite, and 42 transposons were identified in G7. Comparing to the genome of the B. subtilis wild type strain NCIB 3610T, G7 genome contains many genomic translocations, inversions, and insertions, and twice the amount of genomic Islands (GIs), with 42.5% of GI genes encoding hypothetical proteins. G7 possesses abundant putative virulence genes associated with adhesion, invasion, dissemination, anti-phagocytosis, and intracellular survival. Experimental studies showed that G7 was able to cause mortality in fish and mice following intramuscular/intraperitoneal injection, resist the killing effect of serum complement, and replicate in mouse macrophages and fish peripheral blood leukocytes. Taken together, our study indicates that G7 is a B. subtilis isolate with unique genetic features and can be lethal to vertebrate animals once being introduced into the animals by artificial means. These results provide the first insight into the potential harmfulness of deep-sea B. subtilis.